PENGARUH VARIASI KETEBALAN DAN NILAI KOEFISIEN ABSORBSI UNTUK CACAHAN HALUS DAN CACAHAN KASAR PAPAN AKUSTIK DARI BATANG KELOR (MORINGA OLEIFERA LAM) - Fitria Jasman; Sahara Sahara; Muh Said L; Hernawati Hernawati (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the effect of thickness on the absorption coefficient of the acoustic board made from Moringa stems (Moringa Oleifer Lam). The method used in this research is to make an acoustic board with two types of samples, namely finely chopped samples and coarse chopped samples with a thickness of 0.70 cm, 1.00 cm and 1.20 cm, and measuring the absorption coefficient with variations in the thickness of the acoustic board. The frequency values used are 300 Hz, 500 Hz, 750 Hz, 900 Hz, 1000 Hz and 3000 Hz. Based on the results of the study, it was found that the sound absorption coefficient of acoustic material with variations in thickness indicated that the finely chopped and coarsely chopped samples had an effect on increasing the thickness of a sample, where the thicker the sample, the lower the absorption coefficient value. That meets ISO standards sound absorption coefficient value for fine pieces is at a frequency of 500 Hz with an absorption coefficient of 0.35, 0.30, and 0, 019, for 500 Hz with absorption coefficients 0.34, 0.27, and 0.30 while for 900 Hz the absorption coefficient values are 0.32, 0.24, and 0.20.